Libretto jako (u)twór. Zagadnienia genologiczne i metodologiczne – zarys problematyki - Walczak, Jakub (Wydawnictwo Naukowe UAM, 2014)
This article deals with issues connected with defining the libretto in the light of genre classification and the function that libretti perform as part of musical compositions. Libretti, which are marginalized by both literary theory and musicological research, are considered to be dependent texts even though most libretti are compositionally complete and can be analyzed by using the concepts of literary theory. At the same time, although the libretto is not an independent genre, it has its own subgenres which are identified based on the subject matter, function and structural properties (e.g. tragedy, comedy and farce).
The libretto as a genre: problems and approaches